1979
DOI: 10.2136/sssaj1979.03615995004300060012x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Gaseous Nitrogen Products of Denitrification in a Silt Loam Soil

Abstract: The amount and relative proportion of N2 and N2O evolved from a nitrate‐amended surface soil under an atmosphere of He in the range of 7 to 75°C was examined. The objective was to evaluate the effect of temperature on N2O evolution and investigate the optimal temperature for denitrification. The soil had 2.43% organic C and pH of 6.8. Incubations were performed in all‐glass systems which were sealed throughout the incubation period. Denitrification products (N2O, NO, and N2) were determined periodically by gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(68 citation statements)
references
References 0 publications
9
57
2
Order By: Relevance
“…High night-time CO 2 emissions, which were observed over the winter-autumn period, also indicated that the heterotrophic microbial community was highly active during this period (Fig. 3b); such adaptation of microbial populations to various regional climatic zones has been described by other researchers (Keeney et al 1979). Indeed, even under freezing conditions, biological activity and N 2 O emissions have been observed (Rõver et al 1998).…”
Section: Effect Of Soil Environment (Wfps and Temperature) On N 2 O Psupporting
confidence: 71%
“…High night-time CO 2 emissions, which were observed over the winter-autumn period, also indicated that the heterotrophic microbial community was highly active during this period (Fig. 3b); such adaptation of microbial populations to various regional climatic zones has been described by other researchers (Keeney et al 1979). Indeed, even under freezing conditions, biological activity and N 2 O emissions have been observed (Rõver et al 1998).…”
Section: Effect Of Soil Environment (Wfps and Temperature) On N 2 O Psupporting
confidence: 71%
“…Although the final product of denitrification is the benign atmospheric gas N 2 , this process is not always completed and variable amounts of N 2 O, a potent greenhouse gas (GHG), can be produced. Physical, chemical and biological factors influence the reduction of N 2 O to N 2 (Weier et al, 1993) including soil moisture content (Davidson, 1991;Ruser et al, 2006), pH (Simek and Cooper, 2002;Cuhel et al, 2010), temperature (Bailey, 1976;Keeney et al, 1979), C supply (Parkin, 1987;Mathieu et al, 2006), soil redox conditions (Firestone and Tiedje, 1979;Tiedje, 1988) and management (Frolking et al, 1998;Liu et al, 2007).…”
Section: K L Mcgeough Et Al: the Effect Of Cattle Slurry In Combinmentioning
confidence: 99%
“…This temperature was the minimum value above which N 2 O fluxes were observed (Keeney et al, 1979). However, this low temperature did not limit N 2 O flux under the study conditions.…”
Section: Resultsmentioning
confidence: 72%